Conflict and negotiation in Colombia : Are pre-donations useful? (2013)
We model conflict between two agents in which each one has two possible strategies: cease-fire or rejection of the truce. We use the concept of pre-donations, namely, a redefinition of the game in which each agent commits to transfer a share of its output to the other agent (Sertel, 1991). Conditions are established under which a system of pre-donations may facilitate a truce. In particular, for conflicts involving high costs there is a distributive mechanism, acceptable for both parties, whereby cease-fire is the best strategy for both of them. However, in many cases the conditions are not right for such a scheme of pre-donations to be effective. Some limitations of the framework are analyzed and the model is extended to deal with certain shortcomings in the basic setup. To illustrate the relevance of the theoretical results, we briefly describe the circumstances that have characterized the negotiation processes between the Colombian government and various illegal groups in this long-lasting armed conflict. © 2013 The Authors.